IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PRODUKTIVITAS DAN EFEKTIVITAS MADRASAH (Studi Komparatif di MAN 1 Tangerang dan MAN 2 Tangerang) - Ahmad Bahtiar Rifai (Sekolah Tinggi Pariwisata Mataram, 2022)
Find the right type of leadership to be apply in a school organization is a challenge in it self. Transformational leadership style is one of the choices due to the demand of organizational dynamics that prioritize the empowerment of human resource compare to carrying out what the leader demand alone. This study aim to find out how far the implementation of transformational leadership is, the obstacles faced, and find solution that can be give at MAN 1 Tangerang and MAN 2 Tangerang School. This research is a comparative study. Data obtained from observation in the field, interview, and documentation. The result showed that the implementation of transformational leadership in MAN 1 Tangerang and MAN 2 Tangerang is a leadership style that is in accordance with the concept and philosophy of MAN 1 Tangerang and MAN 2 Tangerang. change and brought MAN 1 Tangerang and MAN 2 Tangerang to achieve good achievements. The principal becomes a role model who is respected, valued, and trusted. The principal is able to build a spirit of togetherness and discipline and motivate teachers and employees to work optimally. Principal dare to make changes through creative and innovative actions. Finally, the principal is able to build organizational awareness in teachers and employees by developing an attitude of belonging and a sense of responsibility to achieve the highest achievement